RENCANA INDUK SISTEM PROTEKSI KEBAKARAN (RISPK) KABUPATEN BADUNG TAHUN 2024 - 2034 - I MADE SASTRA WIBAWA; A.A. GEDE SUTRISNA WIJAYA PUTRA; TJOKORDA ISTRI PRAGANINGRUM; I NYOMAN ADI WIRATMA; I MADE BRAM SARJANA; I GEDE MERTA YOGA PRATAMA (GANEC SWARA, 2024)
The Badung Regency Fire Protection System Master Plan (RISPK) for 2024-2034 is a guideline for the Badung Regency Government in carrying out planning, budgeting and formulating policies for preventing, mitigating, protecting and saving the community from fire disasters. The objectives of the RISPK research are (1) to analyze mapping, systems, mechanisms and procedures for fire prevention and handling as well as responsive and technology-based rescue; (2) analyze the preparedness, alertness and empowerment of government officials, the community and stakeholders in preventing and handling fires and rescue and; (3) prevent and/or minimize material losses and casualties, disruption of supply chains, goods/services production processes, environmental damage and disruption of public peace due to fire. The research uses qualitative descriptive methods, the research location is Badung Regency. The research results found; (1) using seven parameters in mapping Badung Regency's fire potential; (2) use Standard Operating Procedures (SOP) as a guide in carrying out responsive, systematic and planned fire prevention and handling efforts and; (3) protecting fire disasters requires a holistic and comprehensive cooperation pattern, involving the government, community, business world and other stakeholders